Hubungan Lingkungan Sekolah dengan Prestasi Akademik Siswa Kelas Tinggi SD Inpres 5/81 Pasaka Kecamatan Sibulue Kabupaten Bone - Endah Purwandari; H. Abd Kadir A; Muhammad Awal Nur (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This research is a quantitative research with a correlational type that aims to determine the relationship between the school environment and the academic achievement of high-grade students of SD Inpres 5/81 Pasaka, Sibulue District, Bone Regency. The population in this study amounted to 49 students and all of them were sampled using saturated sampling techniques. Data collection techniques used questionnaires and documentation. Data analysis used descriptive and inferential statistics with non-parametric techniques (Spearman's rho). The results of the study show that: (a) the condition of the school environment is in the good category; (b) The level of academic achievement of high-grade students of SD Inpres 5/81 Pasaka is in the moderate category; (c) There is a positive and significant relationship between the school environment and the academic achievement of high-grade students; (d) The magnitude of the relationship between the school environment and the academic achievement of high-grade students is in the strong category with a correlation coefficient value of 0.689 and a contribution of 47.47%. It can be concluded that the school environment at SD Inpres 5/81 Pasaka is in the good category and has a strong and significant positive relationship with the academic achievement of high-class students with a contribution of 47.47%.